ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI DI INDONESIA MENGGUNAKAN ERROR CORRECTION MODEL (ECM) PERIODE TAHUN 1994.1–2005.4 - Firdayetti SE, MSi; Michel Toni Adrianto (Media Ekonomi, 2011)
The aim of the implementation of this research was to know whether the national income, the interest rate of the fixed deposit, and the interest rate of credit had the influence that was significant or not towards consumption in Indonesia, and whether being gotten by long-term and short relations towards consumption. The methodology that was utilised in this research was the Error Correction Model method (ECM) that from the OLS method, with before carried out steps as follows, that is the test, the integration test and the test of the co-integration approach of the unit root. And the data that was used in this research was the secondary data in a kwartalan manner in the period 1994:1 up to 2005:4. Was based on results of the research that was carried out, then could be concluded that results of the test of the unit root, showed all variable was not yet stationary and just was stationary in the level test of the integration. While results of the co-integration test showed the stationary consumption model so as to be able to be carried out by the test of ECM. And the results of the Error Correction Model test (ECM) showed that in the long term the national income variable had the influence that was significant towards consumption. The interest rate of the Fixed Deposit in the long term and short-term did not have the influence on consumption. The interest rate of Credit in the long term and short-term also did not have the influence that was significant towards consumption.Keywords :Real Consumption, Real GDP, Deposit Interest Rate, Credit Interest